2021
DOI: 10.3390/cancers13133146
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts in Breast Cancer Treatment Response and Metastasis

Abstract: Breast cancer (BrCa) is the leading cause of death among women worldwide, with about one million new cases diagnosed each year. In spite of the improvements in diagnosis, early detection and treatment, there is still a high incidence of mortality and failure to respond to current therapies. With the use of several well-established biomarkers, such as hormone receptors and human epidermal growth factor receptor-2 (HER2), as well as genetic analysis, BrCa patients can be categorized into multiple subgroups: Lumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 182 publications
4
23
1
Order By: Relevance
“…Lastly, it has been reported that cancer-associated fibroblasts contribute to therapy resistance and metastasis, and endothelial cells play an active role in promoting breast cancer proliferation [ 97 ]. With that in mind, HAGM cryogels could be used for MCTS co-cultures of breast cancer cells, fibroblasts, and endothelial cells to better model breast tumor heterogeneity and complexity [ 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it has been reported that cancer-associated fibroblasts contribute to therapy resistance and metastasis, and endothelial cells play an active role in promoting breast cancer proliferation [ 97 ]. With that in mind, HAGM cryogels could be used for MCTS co-cultures of breast cancer cells, fibroblasts, and endothelial cells to better model breast tumor heterogeneity and complexity [ 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the expression level of AUF1 in breast CAFs has a powerful prognostic value for TNBC as well as ER+/Her2− patients. In fact, several lines of evidence point to the key role of CAFs in modulating the response of breast cancer patients to various types of therapies [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TME exerts crucial roles in tumor proliferation, invasion, metastasis, angiogenesis, metabolism, immunosuppression, and drug resistance [ 28 , 29 ]. Being the most important mesenchymal component in the TME, tumor-associated fibroblasts contribute to the pathogenesis of tumors by releasing diverse growth factors, chemokines, and cytokines and participating in the remodeling of the extracellular matrix [ 30 33 ]. Here, TRMT112 expression was discovered to exhibit a positive link to tumor-associated fibroblasts in BRCA, ESCA, UCEC, and COAD.…”
Section: Discussionmentioning
confidence: 99%